Analyzing the Effect of Exposure to COVID-19 Misinformation on Health Behaviors - Laurence, Meiling; Platt, Olivia; Earnshaw, Valerie A. (Advances in Social Sciences Research Journal, 2022)
American news media have become more diverse, siloed, and politically polarized in recent decades, leading Americans with increasingly varied news consumption patterns to receive disparate information. In addition, the accessibility of social media platforms to unreliable users has resulted in misinformation-sharing on many online platforms. This project aims to elucidate the origins of individuals’ COVID-19 pro- and anti-health behaviors — particularly in the context of their news and information consumption — by investigating relationships between self-reported exposure to true and false statements about COVID-19, belief in such statements, and COVID-19 pro- and anti-health behaviors. Furthermore, the effects of primary news sources, time spent on social media, and demographics on these variables were analyzed. COVID-19 statements were drawn from the C.D.C., W.H.O., and public polls by Pew Research Center. To collect data, a 27-question survey was distributed to 250 panelists from the general U.S. population. Relationships between pairs of variables were analyzed using chi-square tests, which showed that exposure to COVID-19 statements had a significant (P < 0.05) effect on belief in statements, exposure to true statements had a significant effect on COVID-19 health behavior scores, and belief in statements had a significant effect on health behavior scores. In addition, time spent on social media, age, and political affiliation, had significant effects on these variables. This project adds to the growing body of research on the effects of information sources on health behaviors and sheds light on the genesis of COVID-19 pro- and anti-health behaviors.